Un acercamiento a modelos productivos interculturales: integración de los saberes locales en la producción de fríjol, maíz y batata biofortificados en la Sierra Nevada - Cordero, Carina; Gómez, Luis Fernando; Ipaz, Claudia; Cubillos, Juan; Rozo, Yanine; Tofiño, Adriana (2023)
In the Sierra Nevada de Santa Marta, farmers and indigenous communities converge under contrasting conditions of soil quality, access to water supply, agroinputs and traditional knowledge linked to the production of beans, corn and sweet potatoes. The objective of this work was to characterize the soil, study the agronomic behavior of biofortified varieties of beans (Phaseolus vulgaris L.), corn (Zea mays L.) and sweet potatoes (Ipomoea batatas L.) established in monoculture in the case of beans and in association for the case of corn-sweet potato, in production plots with agroecological management, conventional management and without management, under two